Resolute zotarolimus‐eluting stent in ST‐elevation myocardial infarction (resolute‐STEMI): A prespecified prospective register from the DAPT‐STEMI trial. Issue 4 (3rd July 2019) - Postma, Warner; Fabris, Enrico; Van der Ent, Martin; Hermanides, Rik; Buszman, Pawel; Von Birgelen C, Clemens; Cook, Stephane; Wedel, Hans; De Luca, Giuseppe; Delewi, Ronak; Zijlstra, Felix; Kedhi, Elvin
Abstract: Objectives: To evaluate the safety and efficacy outcomes after primary percutaneous coronary intervention (pPCI) with second‐generation Resolute™ zotarolimus‐eluting stent (R‐ZES) in patients enrolled in the DAPT‐STEMI Trial (NCT01459627). Background: R‐ZES is one of the most used drug eluting stents worldwide. To date, the safety and efficacy data of this stent in setting of STEMI is limited. Methods: The Resolute‐STEMI is a prespecified prospective register that reports the safety and efficacy of R‐ZES in setting of ST‐Elevation Myocardial Infarction (STEMI) at 6 months for the following endpoints: a composite endpoint of all‐cause mortality, any myocardial infarction (MI), any (unscheduled) revascularization, stroke and TIMI major bleeding, as well as target lesion failure and stent thrombosis (ST). Results: From a total of 1, 100 STEMI patients enrolled in the trial, 998 received a R‐ZES. At 6 months the PE occurred in 42 (4.2%) patients. All‐cause death, MI, revascularization, stroke and TIMI major bleeding was respectively 8 (0.8%), 9 (0.8%), 34 (3.4%), 2 (0.2%), and 4 (0.4%). The rate of target lesion revascularizations involving the culprit lesion was 1.1%. Target lesion failure was 1.5%. The rate of definite ST was 0.5%. The rate of both definite or probable ST was 0.7%. Conclusions: The present analysis is the largest to date reporting short‐term and mid‐term clinical outcomes with the R‐ZES stent in setting of STEMI. At 30 days and 6‐months R‐ZES has an outstanding safety and efficacy even in this high‐risk category of patients.